Fumonisin B1 - Marasas, W. F. O (World Health Organization, 2000)
This book evaluates the risks to human and animal health posed by the consumption of maize and maize-based products contaminated with fumonisin B1. This naturally occurring mycotoxin, produced by the mold Fusarium verticillioides is found in high concentrations throughout the world, and is believed to be the most prevalent and toxic of the fumonisins. Consumption is known to cause two fatal diseases in farm animals. Possible adverse effects on human health are of particular importance in several developing countries, where maize and maize-based products are the staple food for large populations. A section on sources of human exposure considers factors that influence the vulnerability of maize to contamination during growth, storage, and processing. Weather conditions that favor Fusarium kernel rot are noted to cause significant accumulation of fumonisin B1. Studies of the effects of different processing techniques demonstrate the toxin\'s stability. Dry milling results in its distribution into the bran, germ, and flour. In experimental wet milling, fumonisin has been detected in steep water, gluten fibre, and germ but not in the starch. A review of studies on the environmental fate of fumonisin B1 concludes that fumonisins are heat stable, light stable, water soluble, poorly absorbed, poorly metabolized, and rapidly excreted by animals. As a result, most fumonisin is recycled into the environment in a manner that concentrates its spatial distribution. A section on environmental levels and human exposure reviews a large number of studies measuring levels of contamination in maize and maize-based foods for human consumption and in animal feeds. The highest levels of contamination have been recorded in Europe, followed by North America, Africa, Asia, and Latin America. The most extensive section reviews toxicity data from studies in experimental animals and in vitro test systems. Fumonisin B1 has been shown to be hepatotoxic in all animal species tested, and nephrotoxic in several species. The report found no evidence that consumption of fumonisins causes adverse effects on development or reproductive functions in farm animals or humans. Studies in some species indicate an association between exposure and the development of renal and liver cancers. The evaluation also drew on extensive investigations of equine leukoencephalomalacia and porcine pulmonary oedema syndrome, fatal diseases which have been causally linked to the consumption of fumonisin-contaminated feeds. These and other lines of evidence suggest that fumonisin B1 exerts its toxic action by inhibiting cell growth and causing accumulation of free sphingoid bases and alteration of lipid metabolism. The evaluation of effects on human health draws on limited evidence from correlation studies in South Africa and China, and an analytical study from northern Italy, suggesting a link between direct fumonisin exposure and esophageal cancer. Due to weaknesses in all these studies, no firm conclusions could be reached. No confirmed records of acute fumonisin toxicity in humans were available for evaluation. A final section draws attention to the urgent need for more knowledge about the effects of food processing and cooking, especially in developing countries, on levels of contamination for epidemiological studies of adverse health effects, and for better understanding of the mode of toxic action in humans.
Environmental health criteria, ISSN 0250-863X 219
Keywords: Environmental Exposure; Risk Assessment; experimenty na zvířatech; fumonisiny; Mycotoxins; Animal Experimentation; environmentální vědy; hodnocení rizik; kontaminace potravin; Fumonisins; kyseliny karbocyklické; Acids, Carbocyclic; Food Contamination; vystavení vlivu životního prostředí; mykotoxiny; veřejné zdravotnictví